Nursing students' perceptions of desirable leadership qualities in nurse preceptors: A descriptive survey - Zilembo, Melanie; Monterosso, Leanne (eContent Management, 2008)
There is a paucity of literature examining the contest of leadership within the clinical preceptor/undergraduate nursing student relationship and the relevance of this to the clinical learning environment. This study used a mixed methodological survey approach to explore the leadership qualities in nurse preceptors that are considered desirable and contribute to positive practicum experiences from the perspective of 23 undergraduate nurses. Findings showed students both want and need leadership from their preceptors in order to develop psychomotor skill competency and to experience orientation to the real world of nursing care.Gaining insight into the leadership qualities that students perceive as desirable to enhance the practical experience is vital since that practical experience is viewed as the ?making or breaking? of many students and influences retention in undergraduate education and within the profession post registration.